Establishment of bovine chromosome region specific high resolution maps using microdissection - Goldammer, T.; Brunner, R.M.; Kang'a, S.; Hanotte, Olivier H.; Schwerin, M. (Informa UK Limited, 1999)
An alternative approach for the direct analysis of chromosome regions corresponding to economical traits, based on chromosome microdissection, is described. Large fragment clones isolated with primer pairs designed from chromosome fragment-specific DNA sequences were localized by fluorescence in situ hybridization (FISH) to the scraped chromosome region of interest.